CEFR-based English speaking skill self-assessments by Malaysian graduating non-native English speaking students - Razali, Nurul Hidayah; Abdul Latif @ Bapoo, Lilisuriani (Institute of Teacher Education, Penang Campus, 2019)
Malaysians need to acquire the English language which is widely used in various daily activities such as business, education and administration. Previous researches have shown that local university graduates frequently face problems in getting jobs as they are unable to speak confidently. The objective of this research was to explore how final year students from two English medium universities in Malaysia assessed their own speaking skills, based on the Common European Framework of Reference (CEFR) descriptors. A survey was carried out and responded by 133 final year students from a Malaysian Comprehensive English Medium Public University and 100 final year students from a Malaysian Focused English Medium Public University. The outcomes of this study indicated that most of the respondents from the Comprehensive Public University felt that they were at level B2, for spoken interaction and spoken production, while those from the Focused Public University felt that they were at level B1 for the same skills.